Perovskite thin film and preparation method and application thereof

By using ultrasonic action of oxide nanoparticles on the surface of the perovskite film for grinding and combined with heat treatment, the problems of uneven film quality and poor crystallinity are solved, and high-quality perovskite film preparation is achieved, which improves its photoelectric conversion efficiency.

CN120091741APending Publication Date: 2025-06-03HUANENG RENEWABLES CORPORATION LIMITED +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510255205.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

The existing perovskite film preparation methods have problems such as uneven film quality and poor crystallinity, making it difficult to achieve high-quality preparation of large-area films.

Method used

By using ultrasonic action of oxide nanoparticles on the surface of the perovskite film, the amorphous region is removed, the crystallinity of the film surface is enhanced, and the crystallinity and stability of the film are further improved through heat treatment.

Benefits of technology

This method effectively enhances the crystallinity and stability of perovskite films, improves its photoelectric conversion efficiency, and solves the problem of uneven film quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120091741A_ABST
    Figure CN120091741A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite thin film and a preparation method and application thereof, and the preparation method of the perovskite thin film comprises the steps: coating a substrate with a perovskite raw material solution, and then carrying out the annealing treatment, thereby obtaining a first composite material; performing ultrasonic treatment on the first composite material in an anti-solvent containing oxide nanoparticles to obtain a second composite material; and removing the anti-solvent on the second composite material, and then carrying out heat treatment to obtain the perovskite thin film. According to the preparation method of the perovskite thin film, the surface of the perovskite thin film can be polished through the ultrasonic action of the oxide nanoparticles, an amorphous region is removed, and the crystallinity of the surface of the thin film is enhanced; meanwhile, the crystallinity and the stability of the film can be further improved through heat treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of photovoltaic technology, and particularly to a perovskite thin film, a preparation method thereof, and an application thereof. Background Art

[0002] Due to its excellent optoelectronic properties, perovskite thin films are widely used in fields such as solar cells, LED lights, and photodetectors. However, quality control during the preparation of large-area perovskite thin films is crucial, and current preparation methods have problems such as uneven film quality and poor crystallinity. Therefore, it is necessary to develop a new method for preparing perovskite thin films to improve the quality and performance of the films. Summary of the Invention

[0003] In view of this, one object of this application is to provide a method for preparing a perovskite thin film. Through the ultrasonic action of oxide nanoparticles, the surface of the perovskite thin film can be polished, amorphous regions can be removed, and the crystallinity of the film surface can be enhanced. At the same time, heat treatment can further improve the crystallinity and stability of the film.

[0004] Another object of this application is to provide a perovskite thin film.

[0005] Another object of this application is to provide an application of the perovskite thin film.

[0006] To achieve the above objects, the first aspect of this application proposes a method for preparing a perovskite thin film, including:

[0007] Coating a perovskite raw material solution on a substrate, and then performing annealing treatment to obtain a first composite material;

[0008] Ultrasonically treating the first composite material in an anti-solvent containing oxide nanoparticles to obtain a second composite material;

[0009] Removing the anti-solvent on the second composite material, and then performing heat treatment to obtain the perovskite thin film.

[0010] In some embodiments, the oxide includes a metal oxide.

[0011] In some embodiments, the metal oxide includes at least one of aluminum oxide, tin oxide, and nickel oxide.

[0012] In some embodiments, in the anti-solvent containing oxide nanoparticles, the mass ratio of the oxide nanoparticles to the anti-solvent is (0.001 - 10):1.

[0013] In some embodiments, the anti-solvent includes at least one of chlorobenzene, anisole, and ethyl acetate.

[0014] In some embodiments, the power of the ultrasonic treatment is 10 - 500 W, and the time of the ultrasonic treatment is 1 - 60 min.

[0015] In some embodiments, the temperature of the annealing treatment is 100 - 150 °C, and the time of the annealing treatment is 10 min to 1 h.

[0016] In some embodiments, the method for preparing the perovskite thin film further includes a step of preliminarily curing the first composite material before the ultrasonic treatment; the way of the preliminary curing includes at least one of heating, microwave, and infrared.

[0017] In some embodiments, the temperature of the heating is 50 - 200 °C, and the time of the heating is 0.1 - 1 h.

[0018] In some embodiments, removing the antisolvent from the second composite material includes: washing the second composite material, and then purging with an air gun.

[0019] In some embodiments, the temperature of the heat treatment is 100 - 200 °C, and the time of the heat treatment is 10 min to 12 h.

[0020] In some embodiments, in the perovskite raw material solution, the solute is at least one of ABX 3 wherein A is a methylamine group, a formamidine group or Cs, B is Pb, Sn or Ge, X is I, Br or Cl, and the solvent is at least one of dimethylformamide, dimethyl sulfoxide, N,N - dimethylacetamide, and N - methylpyrrolidone.

[0021] In some embodiments, the substrate includes at least one of glass, a silicon wafer, and a flexible conductive substrate.

[0022] In some embodiments, the method for preparing the perovskite thin film further includes a step of preparing a perovskite raw material solution.

[0023] In some embodiments, the thickness of the coating is 100 - 1200 μm.

[0024] The second aspect of the present application provides a perovskite thin film prepared by the method for preparing a perovskite thin film described in the present application.

[0025] The third aspect of the present application relates to the application of the perovskite thin film described in the present application in the fields of solar cells, LED lights, photodetectors, etc.

[0026] The method for preparing the perovskite thin film described in the present application can at least bring the following beneficial effects:

[0027] 1. The surface of the perovskite film can be polished by the ultrasonic action of oxide nanoparticles to remove the amorphous regions and enhance the crystallinity of the film surface. At the same time, heat treatment can further improve the crystallinity and stability of the film.

[0028] 2. The perovskite film prepared by the method for preparing a perovskite film described in this application has a higher photoelectric conversion efficiency due to its excellent crystallinity and stability.

[0029] Additional aspects and advantages of this application will be given in part in the following description, become apparent in part from the following description, or be learned through the practice of this application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The above and / or additional aspects and advantages of this application will become apparent and be readily understood from the following description of the embodiments in conjunction with the drawings,

[0031] wherein:

[0032] Figure 1 is a current density-voltage curve graph of a solar cell containing the perovskite film prepared in Example 1.

[0033] Figure 2 is a comparative X-ray diffraction (XRD) spectrum of the crystallinity of the perovskite film (experimental group) prepared in Example 1 and the perovskite film (control group) prepared in Comparative Example 1.

[0034] Figure 3 is a schematic structural diagram of the solar cell involved in the optoelectronic performance test.

[0035] Reference numerals:

[0036] 1 - Substrate; 2 - Front electrode; 3 - Hole transport layer; 4 - Perovskite absorption layer; 5 - Electron transport layer; 6 - Barrier layer; 7 - Back electrode. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0037] The embodiments of this application will be described in detail below. The embodiments are exemplary and are intended to explain this application and should not be construed as limiting this application.

[0038] In this application, the disclosure of a numerical range includes all values within the entire range and the disclosure of further sub-ranges, including the endpoints and sub-ranges given for these ranges.

[0039] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are raw materials and equipment that can be obtained through commercial channels or prepared by known methods; the methods involved, unless otherwise specified, are conventional methods.

[0040] When the term "and / or" is used in a list of two or more items, it means that any one of the listed items can be used alone or in combination with any one or more of the listed items. For example, the expression "A and / or B" is intended to mean A or B or A and B, that is, it means only A, only B, or a combination of A and B.

[0041] The method for preparing a perovskite thin film according to an embodiment of the present application includes the following steps:

[0042] S101. Coating a perovskite raw material solution on a substrate, and then performing annealing treatment to obtain a first composite material.

[0043] In an embodiment of the present application, the composition of the perovskite raw material solution is not limited, and it can be the composition of any perovskite raw material solution of resins in the art.

[0044] In some embodiments, the method for preparing the perovskite thin film further includes a step of preparing a perovskite raw material solution.

[0045] Exemplarily, in the perovskite precursor solution, the solute is at least one of ABX 3 wherein A is a methylamine group, a formamidine group or Cs, B is Pb, Sn or Ge, X is I, Br or Cl, and the solvent is at least one of dimethylformamide (i.e., N,N-dimethylformamide, DMF), dimethyl sulfoxide (DMSO), N,N-dimethylacetamide, and N-methylpyrrolidone.

[0046] Exemplarily, the method for preparing the above perovskite precursor solution is: an anti-solvent method.

[0047] As an alternative example, the method for preparing the above perovskite precursor solution is: dissolving lead iodide, lead bromide, formamidine iodide and cesium iodide with a molar ratio of 0.85:0.15:0.78:0.22 in a mixed solution with a volume ratio of DMF and DMSO of 4:1 and mixing uniformly to obtain a perovskite precursor solution.

[0048] In some embodiments, the substrate includes but is not limited to at least one of glass, a silicon wafer, a flexible conductive substrate or other suitable carrier materials.

[0049] In some embodiments, the thickness of the coating is 100 - 1200 μm, including but not limited to 200 μm, 300 μm, 500 μm, 800 μm or 1000 μm, etc.

[0050] Exemplarily, the coating method includes at least one of doctor blading, spraying, etc.

[0051] In some embodiments, the temperature of the annealing treatment is 100 - 150 °C, including but not limited to 110 °C, 120 °C, or 135 °C, etc.

[0052] In some embodiments, the time of the annealing treatment is 10 min to 1 h, including but not limited to 20 min, 30 min, or 40 min, etc.

[0053] In some embodiments, the atmosphere of the annealing treatment is an air atmosphere.

[0054] S102. Ultrasonically treat the first composite material obtained in step S101 in an anti-solvent containing oxide nanoparticles to obtain a second composite material.

[0055] In some embodiments, the oxide includes a metal oxide. In the examples of the present application, the oxide can include any metal oxide.

[0056] Exemplarily, the metal oxide includes at least one of, but is not limited to, aluminum oxide, tin oxide, nickel oxide, etc.

[0057] Exemplarily, the particle size range of the oxide nanoparticles is 5 - 50 nm.

[0058] In some embodiments, in the anti-solvent containing oxide nanoparticles, the mass ratio of the oxide nanoparticles to the anti-solvent is (0.001 - 10):1, including but not limited to 0.001:1, 0.05:1, 0.1:1, 1:1, 5:1, or 8:1, etc.

[0059] In the examples of the present application, when the mass ratio of the oxide nanoparticles to the anti-solvent is within the above range, the etching degree of the oxide nanoparticles on the film surface is moderate and the roughness is appropriate; when it is lower than 0.001:1, the etching of the nanoparticles on the film surface is insufficient; when it is higher than 10:1, the film surface is severely eroded and the roughness is increased.

[0060] As a preferred example, the mass ratio of the oxide nanoparticles to the anti-solvent is (0.01 - 0.5):1, including but not limited to 0.01:1, 0.05:1, or 0.1:1, etc.

[0061] In some embodiments, the anti-solvent includes at least one of, but is not limited to, chlorobenzene, anisole, ethyl acetate, etc.

[0062] In some embodiments, the power of the ultrasonic treatment is 10 - 500 W, including but not limited to 50 W, 100 W, 200 W, 300 W, or 400 W, etc.

[0063] In some embodiments, the time of the ultrasonic treatment is 1 - 60 min, including but not limited to 10 min, 20 min, 30 min, or 40 min, etc.

[0064] In some embodiments, the temperature of the ultrasonic treatment is 25 - 150 °C, including but not limited to 30 °C, 50 °C, 60 °C, 80 °C, 100 °C, or 120 °C, etc.

[0065] In the embodiments of the present application, through ultrasonic treatment, the reaction rate and reaction uniformity between the solute in the antisolvent and the surface of the perovskite film are accelerated. Meanwhile, by controlling parameters such as the power and time of the ultrasonic treatment, the morphology and performance of the film can be optimized.

[0066] In some embodiments, in order to further reduce the roughness of the perovskite film formation and improve the battery performance, the method for preparing the perovskite film further includes a step of preliminarily curing the first composite material before the ultrasonic treatment; the way of the preliminary curing includes at least one of heating, microwave, and infrared, and preferably heating.

[0067] In some embodiments, the temperature of the heating is 50 - 200 °C, including but not limited to 60 °C, 80 °C, 100 °C, 120 °C, 150 °C, or 180 °C, etc.

[0068] In some embodiments, the time of the heating is 0.1 - 1 h, including but not limited to 0.2 h, 0.5 h, or 0.8 h, etc.

[0069] S103. Remove the antisolvent on the second composite material obtained in step S102, and then perform heat treatment to obtain the perovskite film.

[0070] In the embodiments of the present application, the function of removing the antisolvent on the second composite material is: to make the film combine tightly with the subsequent composite layer.

[0071] In some embodiments, removing the antisolvent on the second composite material includes: washing the second composite material, and then blowing it with an air gun.

[0072] Exemplarily, the washing liquid used for washing includes at least one of chlorobenzene, anisole, ethyl acetate, etc.

[0073] In some embodiments, the temperature of the heat treatment is 100 - 200 °C, including but not limited to 125 °C, 150 °C, or 175 °C, etc.

[0074] In some embodiments, the time of the heat treatment is 10 min to 12 h, including but not limited to 1 h, 3 h, 6 h, or 9 h, etc.

[0075] In some embodiments, the heat treatment is carried out in an air atmosphere.

[0076] It should be emphasized that in the method for preparing the perovskite thin film according to the embodiment of the present application, the substrate only serves as a support to facilitate the coating of the perovskite raw material solution and has no influence on the properties of the finally formed perovskite thin film. Therefore, under the condition that other conditions remain unchanged, only replacing the substrate material, generally the performance of the finally prepared perovskite thin film is the same.

[0077] The method for preparing the perovskite thin film according to the embodiment of the present application can at least bring the following beneficial effects:

[0078] 1. The surface of the perovskite thin film can be polished by the ultrasonic action of oxide nanoparticles to remove the amorphous region and enhance the crystallinity of the thin film surface; meanwhile, the heat treatment can further improve the crystallinity and stability of the thin film.

[0079] 2. The perovskite thin film prepared by using the method for preparing the perovskite thin film described in the present application has higher photoelectric conversion efficiency due to its excellent crystallinity and stability.

[0080] The perovskite thin film according to the embodiment of the present application is prepared by using the method for preparing the perovskite thin film according to the embodiment of the present application.

[0081] In some embodiments, the thickness of the above-mentioned perovskite thin film is 200 - 1200 nm, including but not limited to 300 nm, 500 nm, 800 nm or 1000 nm, etc.

[0082] The perovskite thin film according to the embodiment of the present application can be widely applied to fields such as solar cells, LED lights, and photodetectors.

[0083] The perovskite thin film and the above-mentioned applications according to the embodiment of the present application all at least have the beneficial effects of the method for preparing the perovskite thin film according to the embodiment of the present application.

[0084] In the following non-limiting examples, some features of the present technology are further illustrated by way of example.

[0085] I. Examples and Comparative Examples

[0086] Example 1

[0087] The method for preparing the perovskite thin film of this example includes the following steps:

[0088] (1) Preparation of perovskite raw material solution: Lead iodide, lead bromide, formamidinium iodide, and cesium iodide with a molar ratio of 0.85:0.15:0.78:0.22 (i.e., lead iodide:lead bromide:formamidinium iodide:cesium iodide = 0.85:0.15:0.78:0.22) were dissolved in a mixed solution of DMF and DMSO with a volume ratio of 4:1 and mixed evenly to obtain a perovskite raw material solution.

[0089] (2) Preparation of the first composite material: At room temperature (25 °C), the perovskite raw material solution prepared in step (1) was spin-coated on a glass with a thickness of 2 mm, and the spin-coating thickness was 100 μm. Subsequently, it was annealed at 120 °C in an air atmosphere for 30 min to obtain the first composite material.

[0090] (3) Preparation of the second composite material: The first composite material obtained in step (2) was heat-treated at 100 °C for 0.5 h, and then placed in 200 mL of an antisolvent containing oxide nanoparticles and ultrasonically treated to obtain the second composite material.

[0091] Among them:

[0092] In the antisolvent containing oxide nanoparticles, the oxide is alumina (Al 2 O 3 ), the particle size range of the oxide is 5 - 50 nm, the mass ratio of the oxide nanoparticles to the antisolvent is 0.05:1, and the antisolvent is anisole.

[0093] The temperature of the ultrasonic treatment is 25 °C, the power of the ultrasonic treatment is 250 W, and the time of the ultrasonic treatment is 30 min.

[0094] (4) The second composite material obtained in step (3) was washed 3 times with anisole, then purged with an air gun for 10 s, and placed on a constant temperature heating table and heat-treated at 150 °C in an air atmosphere for 0.1 h to obtain the perovskite thin film of this example, with a thickness of 700 nm.

[0095] Example 2

[0096] This example is basically the same as Example 1, except that:

[0097] In step (3), the mass ratio of the oxide nanoparticles to the antisolvent is 0.01:1.

[0098] Example 3

[0099] This example is basically the same as Example 1, except that:

[0100] In step (3), the mass ratio of the oxide nanoparticles to the antisolvent is 0.5:1.

[0101] Example 4

[0102] This embodiment is basically the same as Embodiment 1, except that:

[0103] In step (3), in the anti-solvent containing oxide nanoparticles, the oxide is alumina (Al 2 O 3 ), the particle size range of the oxide is 5 - 50 nm, and the anti-solvent is ethyl acetate.

[0104] Embodiment 5

[0105] This embodiment is basically the same as Embodiment 1, except that:

[0106] In step (3), in the anti-solvent containing oxide nanoparticles, the oxide is a mixture of alumina (Al 2 O 3 ) and tin oxide (SnO 2 ) mixed in a mass ratio of 1:1.

[0107] Embodiment 6

[0108] This embodiment is basically the same as Embodiment 1, except that:

[0109] In step (3), the temperature of the ultrasonic treatment is 25 °C, the power of the ultrasonic treatment is 10 W, and the time of the ultrasonic treatment is 10 min.

[0110] Embodiment 7

[0111] This embodiment is basically the same as Embodiment 1, except that:

[0112] Step (3) is: placing the first composite material obtained in step (2) in 200 mL of an anti-solvent containing oxide nanoparticles for ultrasonic treatment to obtain a second composite material.

[0113] Wherein:

[0114] In the anti-solvent containing oxide nanoparticles, the oxide is alumina (Al 2 O 3 ), the particle size range of the oxide is 5 - 50 nm, the mass ratio of the oxide nanoparticles to the anti-solvent is 0.05:1, and the anti-solvent is anisole.

[0115] The temperature of the ultrasonic treatment is 25 °C, the power of the ultrasonic treatment is 250 W, and the time of the ultrasonic treatment is 30 min.

[0116] Comparative Example 1

[0117] This comparative example is basically the same as Embodiment 7, except that:

[0118] In step (3), the anti-solvent does not contain oxide nanoparticles. That is:

[0119] Step (3) is: placing the first composite material obtained in step (2) into 200 mL of an anti-solvent and performing ultrasonic treatment to obtain a second composite material.

[0120] Wherein:

[0121] The anti-solvent is anisole.

[0122] The temperature of the ultrasonic treatment is 25 °C, the power of the ultrasonic treatment is 250 W, and the time of the ultrasonic treatment is 30 min.

[0123] Comparative Example 2

[0124] This comparative example is basically the same as Example 7, except that:

[0125] Steps (3) and (4) are combined as:

[0126] Placing the first composite material obtained in step (2) into 200 mL of an anti-solvent containing oxide nanoparticles and performing heat treatment while performing ultrasonic treatment, then washing the second composite material obtained in step (3) 3 times with anisole and then purging with an air gun for 10 s to obtain the perovskite film of this comparative example.

[0127] Among them, the temperature of the ultrasonic treatment is 100 °C, the power of the ultrasonic treatment is 250 W, the time of the ultrasonic treatment is 30 min; the temperature of the heat treatment is 100 °C, the time of the heat treatment is 0.1 h, and the composition of the anti-solvent containing oxide nanoparticles is the same as that of Example 8.

[0128] II. Performance testing

[0129] 1. Crystallinity

[0130] The crystallinity of the perovskite films prepared in Example 1 and Comparative Example 1 was respectively tested by X-ray diffraction (XRD), and the test results are as Figure 2 shown. It can be seen from Figure 2 that compared with Comparative Example 1, the perovskite peak intensity of the perovskite film prepared in Example 1 increases, indicating that the crystallization of its perovskite film is enhanced.

[0131] 2. Photoelectric performance

[0132] The perovskite films prepared in each example and comparative example were used to prepare solar cells, and then the photoelectric performance (short-circuit current density, open-circuit voltage, fill factor, photoelectric conversion efficiency) of each solar cell was tested. The test method is: I-V test.

[0133] Among them, as Figure 3As shown, the solar cell includes a substrate 1, a front electrode 2, a hole transport layer 3, a perovskite absorption layer 4, an electron transport layer 5, a blocking layer 6, and a back electrode 7 that are sequentially stacked. The substrate 1 is a transparent glass; the front electrode 2 is an indium tin oxide (ITO) film with a thickness of 150 nm; the hole transport layer 3 is NiO with a thickness of 20 nm; the perovskite absorption layer 4 is a perovskite thin film prepared in each example or comparative example with a thickness of 650 nm; the electron transport layer 5 is C60 with a thickness of 18 nm; the blocking layer 6 is BCP (Bathocuproine, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) with a thickness of 3 nm; the back electrode 7 is a Cu electrode with a thickness of 60 nm.

[0134] The preparation method of the solar cell includes the following steps:

[0135] S1. Sequentially use deionized water, acetone, optical glass cleaner, and isopropanol to ultrasonically clean the transparent glass substrate, and dry it in an oven at 60 °C for 6 h.

[0136] S2. On the transparent glass substrate cleaned in step S1, form a front electrode indium tin oxide (ITO) film by thermal evaporation.

[0137] S3. Use the spin coating method to prepare a hole transport layer on the surface of the front electrode away from the substrate to obtain a first composite.

[0138] S4. Take the first composite obtained in step S3 as the substrate, replace the glass in the preparation method of each example or comparative example, and use the preparation method of each example or comparative example to prepare a perovskite thin film on the side of the first composite away from the transparent glass substrate to obtain a second composite.

[0139] S5. Use the vacuum evaporation method to prepare an electron transport layer on the side of the second composite obtained in step S4 away from the transparent glass substrate to obtain a third composite.

[0140] S6. Use the vacuum evaporation method to prepare a blocking layer on the side of the third composite obtained in step S5 away from the transparent glass substrate to obtain a fourth composite.

[0141] S7. On the side of the fourth composite obtained in step S6 away from the transparent glass substrate, use the vacuum evaporation method to prepare a back electrode, and thus obtain the solar cell.

[0142] The results of the optoelectronic performance test are as Figure 1 shown in Table 1.

[0143] Table 1 Test results of the perovskite thin films prepared in each example and comparative example

[0144]

[0145] As can be seen from Table 1, when the mass ratio of the oxide nanoparticles to the antisolvent is 0.05:1 and the antisolvent is anisole, the optoelectronic performance is the best. Within the scope defined in this application, moderately increasing the content of the oxide nanoparticles in the antisolvent is beneficial to improving the photoelectric conversion efficiency. However, if the increase is excessive, the photoelectric conversion efficiency will slightly decrease. Changing the type of the antisolvent has little effect on the device performance.

[0146] In this application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples", etc. mean that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of this application. In this specification, the schematic descriptions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in a suitable manner in any one or more embodiments or examples. In addition, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.

[0147] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. Thus, the features defined with "first" and "second" can explicitly or implicitly include at least one of the features. In the description of this application, "a plurality of" means at least two, such as two, three, etc., unless otherwise specifically and clearly defined.

[0148] Although the embodiments of this application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be construed as limiting this application. Those of ordinary skill in the art can make changes, modifications, substitutions, and variations to the above embodiments within the scope of this application.

Claims

1. A method for preparing a perovskite film, characterized in that: include: The perovskite raw material solution is coated on the substrate, followed by annealing to obtain a first composite material; Ultrasonic treatment of the first composite material in an anti-solvent containing oxide nanoparticles to obtain a second composite material; The anti-solvent on the second composite material is removed, followed by heat treatment to obtain the perovskite film.

2. The preparation method according to claim 1, characterized in that: The oxides include metal oxides.

3. The preparation method according to claim 2, characterized in that: The metal oxide includes at least one of aluminum oxide, tin oxide and nickel oxide.

4. The preparation method according to claim 1, characterized in that: In the anti-solvent containing oxide nanoparticles, the mass ratio of the oxide nanoparticles to the anti-solvent is (0.001-10):1; And / or, the anti-solvent includes at least one of chlorobenzene, anisole, and ethyl acetate.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The power of the ultrasonic treatment is 10-500W, and the time of the ultrasonic treatment is 1-60min; and / or, The annealing treatment temperature is 100-150° C., and the annealing treatment time is 10 min to 1 h.

6. The preparation method according to any one of claims 1 to 4, characterized in that: The method for preparing the perovskite film further comprises the step of preliminarily curing the first composite material before the ultrasonic treatment; the preliminarily curing method comprises at least one of heating, microwave and infrared.

7. The preparation method according to claim 6, characterized in that: The heating temperature is 50-200° C., and the heating time is 0.1-1 h.

8. The preparation method according to any one of claims 1 to 4, characterized in that: The removing the anti-solvent on the second composite material comprises: washing the second composite material and then purging it with an air gun; and / or, the temperature of the heat treatment is 100-200° C., and the time of the heat treatment is 10 min to 12 h; and / or, In the perovskite raw material solution, the solute is at least one of ABX3, wherein A is a methylamine group, a formamidine group or Cs, B is Pb, Sn or Ge, X is I, Br or Cl, and the solvent is at least one of dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, and N-methylpyrrolidone; And / or, the substrate includes at least one of glass, silicon wafer, and flexible conductive substrate; And / or, the method for preparing the perovskite film further comprises the step of preparing a perovskite raw material solution; And / or, the coating has a thickness of 100-1200 μm.

9. A perovskite film, characterized in that: The method is described in any one of claims 1 to 8.

10. Application of the perovskite film as claimed in claim 9 in the fields of solar cells, LED lamps and photodetectors.

Citation Information

Cited By

  • Perovskite / carbon quantum dot composite photosensitive material and preparation method thereof

    CN121914714A